2022
DOI: 10.1136/heartjnl-2021-320526
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular function across the spectrum of health and disease

Abstract: Knowledge of right ventricular (RV) structure and function has historically lagged behind that of the left ventricle (LV). However, advancements in invasive and non-invasive evaluations, combined with epidemiological analyses, have advanced the current understanding of RV (patho)physiology across the spectrum of health and disease, and reinforce the centrality of the RV in contributing to clinical outcomes. In the healthy heart, ventricular-arterial coupling is preserved during rest and in response to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The normal right ventricle is thin-walled, low afterload, and high-compliance distinct from the left ventricle. Anatomic and functional characteristics determine that the right ventricle is more capable of accommodating the volume overload rather than pressure overload ( Edward et al, 2022 ). In PAH, as a consequence of persistently elevated PAP, the RV afterload and wall stress are increased resulting in RV hypertrophy, dilation, and dysfunction under suitable conditions, and the severity is affected by the duration of the pressure overload.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal right ventricle is thin-walled, low afterload, and high-compliance distinct from the left ventricle. Anatomic and functional characteristics determine that the right ventricle is more capable of accommodating the volume overload rather than pressure overload ( Edward et al, 2022 ). In PAH, as a consequence of persistently elevated PAP, the RV afterload and wall stress are increased resulting in RV hypertrophy, dilation, and dysfunction under suitable conditions, and the severity is affected by the duration of the pressure overload.…”
Section: Discussionmentioning
confidence: 99%
“…In PAH, as a consequence of persistently elevated PAP, the RV afterload and wall stress are increased resulting in RV hypertrophy, dilation, and dysfunction under suitable conditions, and the severity is affected by the duration of the pressure overload. Interestingly, abundant literature demonstrated that RV structure and function in people lacking cardiopulmonary disease vary with age, gender, race, exercise ( Kawut et al, 2011 ; Cornwell et al, 2020 ; Thenappan and Weir, 2020 ; Edward et al, 2022 ). Therefore, it is easy to understand the divergent responses of RV to PH subtypes with different pathogenesis and pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Right HF and TR are debilitating conditions strongly affecting quality of life, hospitalization rates and survival. 38 as parts of a multi-organ syndrome involving cardiac (i.e. right heart chambers, TV apparatus) and extra-cardiac structures (i.e.…”
Section: Clinical Presentation and Coursementioning
confidence: 99%
“…Right HF and TR are debilitating conditions strongly affecting quality of life, hospitalization rates and survival 38 . They can be considered as parts of a multi‐organ syndrome involving cardiac (i.e.…”
Section: Clinical Presentation and Coursementioning
confidence: 99%
“…CMR is currently the imaging modality of choice to assess RV function with high reproducibility. Adverse RV remodelling is common in HF and DCM, and studies are continuing to unravel the clinical relevance of such changes [ 69 , 70 ]. In 250 DCM patients followed up over a median of 6.8 years, RV systolic dysfunction (RVSD), defined by a RV EF ≤ 45% by CMR, was a significant independent predictor of all-cause mortality or cardiac transplantation in DCM patients (hazard ratio, 3.90; 95% CI: 2.16–7.04; p < 0.001) [ 71 ]…”
Section: Risk Stratification By Cmrmentioning
confidence: 99%